2020
DOI: 10.1039/c9tb02814e
|View full text |Cite
|
Sign up to set email alerts
|

Nanoclay-functionalized 3D nanofibrous scaffolds promote bone regeneration

Abstract: A nanoclay-enriched 3D nanofibrous biomimetic scaffold with strong bone regenerative ability by virtue of its improved mechanical properties, osteoconductivity, and drug binding capacity was developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 44 publications
1
24
0
Order By: Relevance
“…Xavier et al [ 27 ] prepared GelMA-XLS hydrogel, improved the mechanical property and degradation behavior of hydrogels and the ALP activity and formation of mineralized nodulus of MC3T3-E1 cells were enhanced in normal culture media with the addition of 2 wt% XLS. Our previous study demonstrated that the degradation products of XLS, i.e., SiO 4 4− , Mg 2+ and Li + combined with the strong binding ability of XLS contributed to the improved osteogenic differentiation [ 49 ] (see Fig. 11 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Xavier et al [ 27 ] prepared GelMA-XLS hydrogel, improved the mechanical property and degradation behavior of hydrogels and the ALP activity and formation of mineralized nodulus of MC3T3-E1 cells were enhanced in normal culture media with the addition of 2 wt% XLS. Our previous study demonstrated that the degradation products of XLS, i.e., SiO 4 4− , Mg 2+ and Li + combined with the strong binding ability of XLS contributed to the improved osteogenic differentiation [ 49 ] (see Fig. 11 ).…”
Section: Resultsmentioning
confidence: 99%
“…The incorporation of XLS not only increased the stiffness of BG scaffolds, but also enhanced osteogenic differentiation of stem cells . The enhanced osteogenic abilities of XLS were mainly due to two reasons: firstly, the XLS can strongly binding with pro-osteoblastic factors, such as BMPs; secondly, the degradation products from XLS also had positive effects on the osteogenesis of stem cells [ 21 , 49 , 50 ]. Moreover, the elevated HIF-1α and VEGF expressions in ADSCs in vitro suggested the BG-XLS/GelMA-DFO scaffolds had the ability to promote angiogenesis likely through hypoxia mimicking agent activated HIF- 1α signaling pathway [ 16 ].…”
Section: Resultsmentioning
confidence: 99%
“…fabricated a Laponite RD‐reinforced 3D gelatin nanofibrous scaffolds via a thermally induced phase separation methodology together with particle leaching. [ 86 ] BMP‐2 was subsequently added to the construct in order to improve bone regeneration ability. In vivo bone regeneration studies demonstrated that those scaffolds with the clay and BMP‐2 resulted in 25.6% new bone area, while the scaffolds without the clay showed only 6.3%.…”
Section: In Vivo Studiesmentioning
confidence: 99%
“…Despite this, the constructs themselves did not demonstrate sufficient power to create bone tissue alone without the help of BMP‐2. [ 86 ]…”
Section: In Vivo Studiesmentioning
confidence: 99%
“…Bone marrow mesenchymal stem cells (BMSCs) is a process comprised of multilineage differentiation capacities, including osteogenesis and chondrogenesis, which has garnered increasing attention over the past decades (Charbord, 2010). Recent experimental studies have revealed that modified mesenchymal stem cells (MSCs) enhance osteogenic commitment and exhibit notable therapeutic implications to promote bone formation and regeneration (Wu, Wang, Wang, Liang, & Li, 2020; Yao, Fuglsby, Zheng, & Sun, 2020). Several factors including bone morphogenetic protein‐2 (Ramazzotti et al, 2016), and runt‐related transcription factor 2 (RUNX2; J. M. Kim et al, 2020), parathyroid hormone (Yang et al, 2019), have been implicated in the process of osteogenic differentiation.…”
Section: Introductionmentioning
confidence: 99%